Biliary panlitiasis in a 60-year-old male patient who underwent a bilioenteric anastomosis and cholecystectomy 13 years ago. Case report - Rivadeneira-Proaño, Francisco (2024)
Introduction: Panlithiasis is define as the presence of multiple stones in the biliary tract that is classified as primary, secondary, or mixed according to the origin of the stones. Management consists of endoscopic retrograde cholangiopancreatography (ERCP), exploration of the biliary tract, or biliodigestive anastomosis (BDA), either choledochoduodenostomy or hepaticojejunostomy. Objective: Describe the clinical case of a patient with biliary panlithiasis, addressing the clinical presentation, diagnostic methods, treatment and evolution, with the purpose of offering a solid resource to the medical community. Case Presentation: We present a 60-year-old male patient who underwent cholecystectomy 13 years ago and has a bilioenteric anastomosis with recurrent panlithiasis. Biliary lavage was performed with the output of stones and pus from the inside. Finally, a Kehr tube was placed along with clinical treatment. The patient showed a favorable outcome. Discussion: This case revealed a panlithiasis upon exploration of the biliary tract under endoscopic vision. Despite finding no obstruction, the patient had a history of cholecystectomy and a hepatic-jejunal diversion due to iatrogenic injury. The treatment decision should be multidisciplinary, as each case is unique and depends on the patient's characteristics and individual clinical conditions. Conclusions: Recurrent choledocholithiasis required strict pharmacological control to prevent recurrence and subsequent exploration of the biliary tract, which increases patient morbidity and mortality. Continuous medical follow-up of the patient and the predisposition with which they have for the formation of stones is important. These can be prevented, identified, and treated in a timely manner.